A new record of Ophioglossum Reticulatim Linn. at Fortchacu III, Kalilangan, Bukidnon - Amoroso, Victor B.; Macabudbud, Florfe L. (1988)
Ophioglossum reticulatum Linn. Is reported to be present on Forthchacu III, Kalilangan, Bukidnon for the first time . Its classification, decription, ecology and distribution are presented.
Includes bibliographical references (page 403)
Keywords: Biology; Ophioglossum Reticulatim; Philippine plants; Philippine Ferns